2010
DOI: 10.1371/journal.pone.0010001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Dependence on ATR and ATM for Double-Strand Break Repair in Human Embryonic Stem Cells and Neural Descendants

Abstract: The DNA double-strand break (DSB) is the most toxic form of DNA damage. Studies aimed at characterizing DNA repair during development suggest that homologous recombination repair (HRR) is more critical in pluripotent cells compared to differentiated somatic cells in which nonhomologous end joining (NHEJ) is dominant. We have characterized the DNA damage response (DDR) and quality of DNA double-strand break (DSB) repair in human embryonic stem cells (hESCs), and in vitro-derived neural cells. Resolution of ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
124
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(134 citation statements)
references
References 44 publications
8
124
0
Order By: Relevance
“…25 Deficits in this key feature are the likely reason for a certain degree of DDR activation observed in proliferating astrocytic lines 26,27 and differentiated astrocytes displaying residual proliferation. 28 Importantly, downregulation of DDR is peculiar of astrocytes and is not necessarily associated with terminal differentiation. Indeed, as a relevant comparison, we show that neurons display a detectable DDR both in in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…25 Deficits in this key feature are the likely reason for a certain degree of DDR activation observed in proliferating astrocytic lines 26,27 and differentiated astrocytes displaying residual proliferation. 28 Importantly, downregulation of DDR is peculiar of astrocytes and is not necessarily associated with terminal differentiation. Indeed, as a relevant comparison, we show that neurons display a detectable DDR both in in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Failed DSB repair or inaccurate DNA repair causes chromosomal rearrangement, chromosome loss, or carcinogenesis [13,14]. In mESCs, DSBs are predominantly repaired through the high-fidelity HR pathway, which occurs throughout the cell cycle [6,15]. The essential role of HR in mESCs is supported by the fact that basal levels of proteins involved in HR are higher in mESCs than in fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the difference in genomic abnormalities between ATM Ϫ/Ϫ cells and H2AX Ϫ/Ϫ cells implies that H2AX HR function may be independent of ATM. In addition, it has been suggested that ATM is dispensable for HR in human embryonic stem cells and neural progenitor cells (30).…”
mentioning
confidence: 99%